Interval-Valued Semiprime Fuzzy Ideals of Semigroups. (4th May 2014) - Kar, Sukhendu; Sarkar, Paltu; Hila, Kostaq
Abstract : We introduce the notion of (i-v) semiprime (irreducible) fuzzy ideals of semigroups and investigate its different algebraic properties. We study the interrelation among (i-v) prime fuzzy ideals, (i-v) semiprime fuzzy ideals, and (i-v) irreducible fuzzy ideals and characterize regular semigroups by using these (i-v) fuzzy ideals.